Cytokines and autologic bone marrow mononuclears in postmyocardial infarction regeneration - V. V. Ryabov; V. A. Markov; Yu. S. Poponina; T. E. Suslova; A. L. Krylov; S. V. Popov; R. S. Karpov (Кардиоваскулярная терапия и профилактика)
Aim. To study safety and effectiveness of autologic bone marrow mononuclears (BMM) transplantation in acute myocardial infarction (AMI) patients. Material and methods. This open, randomized, controlled study included 44 AMI patients: 22 in intervention group (I) and 22 in control group (II). AMI-related coronary artery (AMI-CA) recanalization was performed by stenting. At Day 7-21 of AMI, 100 millions of autologic BMM were infused into AMI-CA in Group I. BMM distribution was studied by radionuclide 99mТс-HMPAO indication method. Clinical status, physical stress tolerance, quality of life were assessed; echocardiography, 24-hour electrocardiography monitoring, myocardial perfusion scintigraphy with 199Tl and ATP were performed. Plasma levels of fatty acid-binding protein, tumor necrosis factor)alpha (TNF)alpha), interleukin 1-beta (IL-1beta), insulin-like growth factor (ILGF), and basic fibroblast growth factor (FGF) were measured. Results. Intracoronary BMM infusion resulted in myocardial BMM fixation. There was no inter-group difference in volume parameters and left ventricular (LV) ejection fraction. In intervention group, local LV contractility improved earlier. Transient perfusion defect remained at 6 months in control group only. In Group I, at Days 1 and 5, the levels of IL-1-beta and TNF-alpha were significantly lower, and ILGF-1 - significantly higher than in controls. BMM quantity directly correlated with basic FGF levels. Conclusion. Cell cardiomyoplastics facilitates myocardial cell fixation, without damaging myocardium, triggering malignant arrhythmias or affecting global LV contractility, reduces IL-1-beta and TNF-alpha levels, increases ILGF-1 and basic FGF concentration.